KETERAMPILAN PROSES SAINS DALAM PEMBELAJARAN TATAP MUKA TERBATAS PADA SISWA SMP - Jihan Adilah; Martini Martini (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This research aimed to analyze students' science process skills (SPS) during limited face-to-face learning in one of the junior high schools in East Java province. The type of this study was descriptive quantitative research. The subjects in this study involved 35 students in VIII grade. The instrument used a science process skills test sheet. Data collection technique used was test that analyzed descriptively. The results of the SPS analysis of students in limited face-to-face learning obtained a score with a high ability category. The highest skill of students was on the indicator of classifying, while the lowest skill of students was on the indicator of formulating a problem. Based on the research that has been done, it can be concluded that the SPS level of students was in the high category so that it can be said that limited face-to-face learning affects the increase in the achievement of students' SPS with high scores.